Images of Italy representation of cities in Italian Photobooks (1950-1980) - Criscione, Miryam (Revelar: Journal of Photography and Image Studies, 2019)
The present contribute intends to focus on some authorial photobooks published in Italy, especially those that have the core of their narrative interest in the representation of the main Italian cities. The photobook is a publication quite different from the most popular touristic guides illustrated by photographs. In fact, it is always an authorial project on a chosen topic where the photographer carries on a predominantly visual discourse. I propose an analysis of the most important photobooks issued between the 195o's and the 198o's, focusing on a case study of Venice and Milan. The purpose of this paper is to compare the representations of these Italian cities during those decades, stressing how their different image is due not only to the different vision of Italian photographers but also to the different layouts of the photobooks, which apart from its content must be considered as a physical object as well.